Profile of extrahepatic portal venous obstruction among children in Central India - Jain, Mayank; Jain, Jenisha; Passi, Gauri Rao; Jain, Kamna; Jain, Shikhar (Clinical and Experimental Hepatology, 2017)
Introduction : There is a paucity of data regarding the clinical profile of children with extrahepatic portal venous obstruction (EHPVO) from Central India. Material and methods : Retrospective analysis of 30 children with EHPVO treated between 2002 and 2012. Results : The median age of presentation was 12.5 years (range 5-14 years) and median duration of symptoms was 3.2 years (range 0.3-10 years). Home delivery was noted in 30 cases (100%), umbilical sepsis in 8 (27%) and history of cow dung application over the umbilical cord in 2 cases (6.7%). Twenty-two cases (73.4%) presented with upper gastrointestinal (GI) bleeding while 18 (60%) were referred for pancytopenia and/or hypersplenism. The patients underwent a median of 3.2 sessions of endoscopic therapy for varices. Most patients (19/30, 63.4%) dropped out of serial endotherapy due to the paucity of funds. Shunt surgery was performed in 7 patients. Conclusions : Home delivery and umbilical sepsis are significant risk factors for EHPVO. Most patients present with GI bleeding and do well on endoscopic treatment/shunt surgery.